An interesting rare case of spontaneous pregnancy with imperforate hymen and high transverse vaginal septum with bicornuate uterus - KR, Bharathi; S., Vijayalakshmi; N., Divya Alamelu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Congenital anatomic disorders of the female reproductive tract may result from genetic mutation, developmental arrest and abnormal hormonal exposure during embryonic development. These anomalies have a huge impact on the woman’s menstrual, sexual and reproductive functions. Pregnancy with these anatomic disorders is quite challenging. Here we present a rare interesting case of spontaneous pregnancy with multiple anatomic disorders namely- imperforate hymen, high transverse vaginal septum and bicornuate uterus.